2012
DOI: 10.1590/s1980-57642012dn06010009
|View full text |Cite
|
Sign up to set email alerts
|

Life quality, depression and anxiety symptoms in chronic post-traumatic headache after mild brain injury

Abstract: Post-traumatic headache (PTH) is the most common symptom found in the post-traumatic syndrome, whose onset occurs within seven days of the trauma. The condition is characterized as acute when it persists for up to 3 months. PTH beyond this period is considered chronic.ObjectivesThe objective of this study was to determine the clinical features of chronic post-traumatic headache (cPTH) and its association with depression, anxiety and quality of life.MethodsA total of 73 female subjects were evaluated. Patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 24 publications
(24 reference statements)
0
11
0
Order By: Relevance
“…In the ICHD-3 criteria, the only evidence for causality between the underlying injury and PTH is the time interval between the injury and headache onset. The ICHD-3 classification committee chose to keep this interval relatively short, to maximize the specificity of the criteria and since data suggest that the majority of PTH does indeed begin within 7 days of injury (5)(6)(7). However, it is recognized that some PTH might begin after the first 7 days (6,8,9).…”
Section: Introductionmentioning
confidence: 99%
“…In the ICHD-3 criteria, the only evidence for causality between the underlying injury and PTH is the time interval between the injury and headache onset. The ICHD-3 classification committee chose to keep this interval relatively short, to maximize the specificity of the criteria and since data suggest that the majority of PTH does indeed begin within 7 days of injury (5)(6)(7). However, it is recognized that some PTH might begin after the first 7 days (6,8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Comparing with the normal weight group (32%), the prevalence was higher in overweight children (39%; odds ratio [OR] 1.35, 95% confidence interval [CI] 0.51‐3.61) and even higher in the obese group (52%; OR 2.25, 95% CI 0.99‐5.12). Metabolic syndrome was found in 25%, and patients with the syndrome did not have higher prevalence of headache (52% vs 45%); (3) In adults, the metabolic syndrome does not appear to influence headache prevalence in obese patients; (4) A score to differentiate migraine from tension‐type headache was established, using 536 headache attacks reported by 121 nurses during a 2‐month follow‐up; (5) 14 new cases of corpalgia in migraine patients were described; (6) The continuous prophylactic use of propranolol, amitryptiline, or simvastatin in migraineurs decreases both the frequency of headache attacks and the production of nitric oxide in the blood; (7) Vitamin B6 has a preventive effect on menstrual migraine when used at a dose of 600 mg/day from the 14th day until menstruation; (8) Clinical symptomatology of the postdural puncture headache and risk factors were evaluated in 640 raquianesthesias; (9) Melatonin‐induced analgesia in addition to inhibiting neoplasic growth using a mouse or rat as the animal model; (10) The history of primary headache is a risk factor of headache related to hemodialysis (52% vs 12%); (11) A descriptive, comparative, cross‐sectional study with 110 postmenopausal women (recent [<5 years] vs late [≥5 years]) showed that the recent postmenopausal group presented highest average scores in the memory/concentration, vasomotor symptoms, and attractiveness domains in the Women's Health Questionnaire for assessment of their quality of life; (12) Prior history of headache is a risk factor of postmastectomy pain (OR 1.92; 95% CI: 1.10‐3.34); (13) Sentinel headache, as warning sign of subarachnoid hemorrhage due to ruptured intracranial aneurysm, was present in 18% of the patients; (14) The characteristics of head pain in response to an experimental cold stimulus to the palate in 414 volunteers were described; (15) Chronic posttraumatic headache after mild traumatic brain injury is similar to migraine in women; (16) There was migraine remission in 35%, 77%, 79%, respectively, in the first, second, and third trimesters among migraine without aura sufferers during pregnancy, and exclusive breastfeeding was associated with a lower chance of migraine recurrence at the first postpartum month; (17) Perfumes, paints, gasoline, and bleach are the most frequent odorants that trigger migraine attacks; Osmophobia predominated in patients with migraine and may be a specific maker to differentiate migraine from tension‐type headache; (18) In a population of 726 children and adolescents, headache was significantly associated with myopia (OR 2.67), hyperopia (OR 3.10), astigmatism (1.86), and strabismus (5.21); (19) Water deprivation is associated with increase of pain in the head in rats; (20) In a study involving 417 university students, 53% of them mentioned they ha...…”
Section: Professor Wilson Farias Da Silva and The Federal University mentioning
confidence: 99%
“…The Federal University of Pernambuco has contributed to the study of headache for almost half a century since the first publication in 1968 . Wilson Farias da Silva, Marcelo Moraes Valença, Pedro Sampaio Rocha Filho, Joaquim Costa Neto, Waldmiro Serva, Fabíola Lys Medeiros, Hugo André Martins, and Daniella Araújo de Oliveira are a few of the researchers that have been involved in the study of different aspects of the diagnosis, physiopathology, and treatment of headache disorders in the Federal University of Pernambuco. Rubem Guedes has also published vast amounts of data on spreading depression, today considered an experimental model to study migraine.…”
Section: Publications In Headache Medicinementioning
confidence: 99%
“…The majority of PTH improve within 6 to 12 months post-injury; however, 18-33% may continue well beyond a year [3], and nearly 25% persist for more than a year [6]. Although PTH can vary in type, the most common of which are phenotypically migraine-like followed by tension-type or other headaches such as cervicogenic headaches [3,5,7,8], PTH in general has debilitating and disruptive effects on normal daily functioning [9][10][11].…”
Section: Introductionmentioning
confidence: 99%